Dental follicle mesenchymal stem cell administration ameliorates muscle weakness in MuSK-immunized mice - AKKOÇ, TUNÇ (BMC, 2015)
Background: Myasthenia gravis (MG) is an antibody-mediated autoimmune disease of the neuromuscular junction (NMJ), mostly associated with acetylcholine receptor (AChR) antibodies. Around 5-10 % of MG patients show antibodies to muscle-specific tyrosine kinase (MuSK). Mesenchymal stem cell (MSC) administration has been shown to ameliorate muscle weakness in the experimental autoimmune myasthenia gravis (EAMG) model induced by AChR immunization. Methods: To investigate the efficacy of stem cell treatment in MuSK-related EAMG, clinical and immunological features of MuSK-immunized mice with or without dental follicle MSC (DFMSC) treatment were compared. Results: MuSK-immunized mice intravenously treated with DFMSC after second and third immunizations showed significantly lower EAMG incidence and severity and reduced serum anti-MuSK antibody, NMJ IgG, and C3 deposit levels and CD11b+ lymph node cell ratios. Moreover, lymph node cells of DFMSC-administered mice showed reduced proliferation and IL-6 and IL-12 production responses to MuSK stimulation. By contrast, proportions of B and T cell populations and production of a wide variety of cytokines were not affected from DFMSC treatment. Conclusions: Our results suggest that DFMSC treatment shows its beneficial effects mostly through suppression of innate immune system, whereas other immune functions appear to be preserved. Stem cell treatment might thus constitute a specific and effective treatment method in MuSK-associated MG.
Keywords: Myasthenia gravis; Muscle-specific kinase; Mesenchymal stem cells; Dendritic cells; Autoimmunity; AUTOIMMUNE MYASTHENIA-GRAVIS; TYROSINE KINASE MUSK; BONE-MARROW; CLINICAL-APPLICATIONS; SUPPRESSION; EXPRESSION; GAMMA